Developing Social Tolerance through a Multidisciplinary Approach in Elementary School Students: The Importance of Social Tolerance in Elementary Education - Fitriyani, Fitriyani; Hidayat, Dede R.; Lestari, Ika (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Social tolerance is an important aspect in character education that needs to be instilled early on, especially in the context of a pluralistic Indonesian society. This article aims to examine the urgency of instilling social tolerance values ​​in elementary school students and to explore the effectiveness of a multidisciplinary approach in supporting the development of tolerant attitudes among students. The research method uses a descriptive qualitative approach, which was conducted at SDN Sertajaya 05 Cikarang, Bekasi Regency. This study is based on development research that has been conducted to develop cognitive moral-based learning media to improve social tolerance attitudes in grade V elementary school students. This study shows that a multidisciplinary approach that integrates Civic Education, Indonesian Language, Social Sciences, and Arts and Culture subjects is able to create an inclusive, participatory, and contextual learning environment. The findings show that value-based learning with a cross-disciplinary approach plays a significant role in strengthening students’ understanding of diversity and improving social and moral skills. This article recommends the active role of teachers in designing cross-subject learning that instills values ​​of tolerance through collaborative activities, discussions, reflections, and community-based projects.